Perencanaan Pemeliharaan Mesin Produksi dengan Menggunakan Total Productive Maintenance untuk Menjamin Kestabilan Proses Produksi - Yusuf Mauluddin; Dewi Rahmawati; Dewi Oktavianti (Jurnal Kalibrasi, 2022)
PT. Perkebunan Nusantara VIII is a business engaged in the production of black tea, commonly called "Orthodox tea" which is still constrained by problems with machine efficiency. Damaged components often occur in Withering Trough machines. This situation can affect delays in the production process in response to reduced production capacity. This research strategy uses the Mix Method approach, where qualitative methods can provide information from interviews and direct observation of machine conditions using Failure Mode and Effects Analysis to determine the order of priority problems that arise, and the sequence of problems will be determined. Using the Overall Equipment Effectiveness technique, data on maintenance and failure of machines connected to manufacturing machines, quantitatively to determine machine performance. Research results show that the OEE value on a 61% engine is still below the Japanese Institute of Plant Maintenance standard for 85% OEE. From the calculation of the Six Big Losses, the biggest average losses are 64% for defects in process and 78% for equipment failures. The RPN value with the highest failure rate is 150.144 with the factor that the engine components are not precise because there is no periodic maintenance carried out on the machine and the operator's lack of response to machine damage.